Astrocytes enhance glioblastoma growth. Issue 2 (11th September 2019) - Mega, Alessandro; Hartmark Nilsen, Mette; Leiss, Lina Wik; Tobin, Nicholas P.; Miletic, Hrvoje; Sleire, Linda; Strell, Carina; Nelander, Sven; Krona, Cecilia; Hägerstrand, Daniel; Enger, Per Ø.; Nistér, Monica; et al.
Abstract: Glioblastoma (GBM) is a deadly disease with a need for deeper understanding and new therapeutic approaches. The microenvironment of glioblastoma has previously been shown to guide glioblastoma progression. In this study, astrocytes were investigated with regard to their effect on glioblastoma proliferation through correlative analyses of clinical samples and experimental in vitro and in vivo studies. Co‐culture techniques were used to investigate the GBM growth enhancing potential of astrocytes. Cell sorting and RNA sequencing were used to generate a GBM‐associated astrocyte signature and to investigate astrocyte‐induced GBM genes. A NOD scid GBM mouse model was used for in vivo studies. A gene signature reflecting GBM‐activated astrocytes was associated with poor prognosis in the TCGA GBM dataset. Two genes, periostin and serglycin, induced in GBM cells upon exposure to astrocytes were expressed at higher levels in cases with high "astrocyte signature score". Astrocytes were shown to enhance glioblastoma cell growth in cell lines and in a patient‐derived culture, in a manner dependent on cell–cell contact and involving increased cell proliferation. Furthermore, co‐injection of astrocytes with glioblastoma cells reduced survival in an orthotopic GBM model in NOD scid mice. In conclusion, this study suggests that astrocytes contribute to glioblastoma growth and implies this crosstalk as a candidate target for novel therapies. Main points: Astrocytes stimulate glioblastoma growth in vitro. A glioblastoma‐associated astrocytes gene signature associates with shorter patient survival. A co‐injection mouse model shows in vivo relevance of the astrocyte‐glioblastoma crosstalk.